Effectiveness of Augmented Reality-Based Therapeutic Patient Education (TPE-AR DM2) Integrated with the Chronic Care Model on The Independence of Posyandu Cadres in Managing Diabetes Mellitus - Novita Fajriyah; Rina Budi Kristiani; Hermanto Wijaya (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Diabetes mellitus is a chronic disease that requires continuous management. Integrated Health Service Post (Posyandu) cadres play a crucial role in supporting community education and mentoring, but their independence is often limited. The implementation of Augmented Reality-based Therapeutic Patient Education (TPE-AR DM2) with the Chronic Care Model (CCM) approach is an innovation expected to increase cadre independence in managing diabetes mellitus. Community service objectives are to determine the effectiveness of implementing TPE-AR DM2 with the CCM approach on Posyandu cadre independence in managing diabetes mellitus. This quasi-experimental study used a pre-test and post-test design involving 25 posyandu cadres as respondents who received the TPE-AR DM2 with ccm intervention over a 5-week intervention period. Cadre independence was measured based on five operational indicators: (1) knowledge, (2) ability to operate the TPE-AR DM2 application, (3) glucometer skills, (4) diabetic foot exercise skills, and (5) therapeutic communication skills. Data analysis used the n-gain test to assess the effectiveness of the intervention. The study showed a significant increase in all indicators of cadre independence after the intervention. The average knowledge score increased from 40.22 to 83.34 (N-gain = 0.72), the ability to operate the TPE-AR DM2 application from 35.96 to 84.72 (N-gain = 0.76), glucometer skills from 45.84 to 85.60 (N-gain = 0.73), diabetic foot exercise skills from 45.84 to 91.60 (N-gain = 0.84), and therapeutic communication skills from 32.02 to 82.60 (N-gain = 0.74). All N-gain values >0.7 indicate the high effectiveness of the intervention in increasing the independence of Posyandu cadres. Conclusion: The implementation of TPE-AR DM2 with the Chronic Care Model approach has been proven effective in increasing the independence of Posyandu cadres in managing diabetes mellitus. This innovation can be a technology-based cadre empowerment strategy to support chronic disease management at the community level.